Facile Construction of Self-Healing Polydopamine-Based Composite Coating Protection of Copper From NaCl Solution - Chen, Wei; Fan, Juanjuan; Jiang, Yueyue; Li, Shouting; Ying, Ye; Yang, Haifeng (Frontiers in Materials, 2022)
Developing a sufficient composite organic inhibitor coating on the surface of metals is a promising strategy to improve the protection capability of metal materials from corrosive media. In this study, dopamine is polymerized into a polydopamine coating on a copper surface by embedding 8-hydroxyquinoline (denoted as PDA@8-HQ). The formation mechanism of PDA@8-HQ on the surface of copper is confirmed by X-ray photoelectron spectroscopy, Fourier transform infrared reflectance, and Raman methods. Electrochemical and field emission scanning electron microscopic results show that the PDA@8-HQ coating made with the addition of 8-HQ was 0.02 M and had the greatest inhibition efficiency (99.1%). When the optimal composite coating is damaged by external forces, self-healing capability could be obviously found due to generating insoluble complex species between corrosive products of copper ions and 8-HQ and the salt solution in the damaged region. This study provides feasibility for the construction of functional corrosion inhibitors on the metal surface.